2020
DOI: 10.4314/gmj.v53i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among in-school adolescents in Yilo Krobo municipality in the Eastern Region of Ghana

Abstract: Background: Adolescent cigarette smoking is of public health importance since many adult smokers had initiated the habit as adolescents. This study aims to determine the prevalence of cigarette smoking among in-school adolescents in Yilo Krobo Municipality, Ghana and factors associated with cigarette smoking. Methods: A school-based cross-sectional analytic study was conducted in February 2017 in Yilo Krobo Municipality in the Eastern Region of Ghana. A stratified random sampling method was applied to select 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this study, adolescents stated that factors such as the importance of the role of friends, having female smoker friends, imitation of friends, and interacting with smokers were effective in their tendency to smoke. The results of the Owusu-Sarpong study showed that smoking of close friends is effective in adolescents starting to smoke [ 29 ]. The results of various studies have shown that smoking by close friends, belonging to a smoking group, pressure from friends/peer group were the influencing factors of adolescent smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, adolescents stated that factors such as the importance of the role of friends, having female smoker friends, imitation of friends, and interacting with smokers were effective in their tendency to smoke. The results of the Owusu-Sarpong study showed that smoking of close friends is effective in adolescents starting to smoke [ 29 ]. The results of various studies have shown that smoking by close friends, belonging to a smoking group, pressure from friends/peer group were the influencing factors of adolescent smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, adolescents reported that factors such as family problems, parental divorce, stressful family environment, inappropriate the role modeling of mothers, use of hookah by parents, lack of proper communication between parents and adolescent, inattention, and parents’ neglect of their child’s smoking were effective in their tendency to smoke. The results of the Owusu-Sarpong study showed that parental divorce is one of the effective factors in tendency of adolescents to smoke [ 29 ]. The results of another study on women showed that family factors, including whether there are smokers in the family, family problems, and family constraints were effective in adolescents’ tendency to smoke [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the total articles, 24 studies were from western sub‐Saharan Africa [5, 32–53], 15 studies were from southern sub‐Saharan Africa [54–68] and 12 studies were from eastern sub‐Saharan Africa [6, 69–79]. Two studies were conducted in multiple regions [11, 80] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Many smokers are initiated into the habit between the ages of 13 and 15 years [ 2 ]. Adolescent smokers are a source of public health importance because many are at risk of future morbidity later in life [ 1 , 5 , 14 ]. In 2000, globally about a third of population aged 15 years and older was used tobacco; whereas this declined to 24.9% by 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Many students will start smoking at college or university. Previous findings have that use of tobacco was affected by age, male sex, place of residence, fraternity, type of family, being unmarried, family income, pocket money, alcohol use, ever khat use, year of study, having friend and family member who smokes, tension reduction, pleasure, number of sticks smoked daily, and peer pressure [ 2 , 4 , 14 , 18 - 22 , 27 ].…”
Section: Introductionmentioning
confidence: 99%